Seychelles : Extended Arrangement-Financing Assurances Review-Staff Report. (IMF Staff Country Reports; Country Report ;, 2011)
The Executive Board approved a three-year Extended Fund Facility with Seychelles. This report briefly outlines performance under the program, including compliance with the end-December targets, before addressing the issue of financing assurances. Macroeconomic performance through end-2009 continued to be encouraging. Prudent fiscal and monetary policies have been key to the strong macroeconomic stabilization. A review of financing assurance has been outlined. Significant progress has also been achieved with remaining non-Paris Club official bilaterals and external commercial banks.